Diverging Discourses: Animal Health Challenges and Veterinary Care in Northern Uganda - Arvidsson, Anna; Fischer, Klara; Hansen, Kjell; Sternberg-Lewerin, Susanna; Chenais, Erika (Frontiers in Veterinary Science, 2022)
People in northern Uganda are currently rebuilding their lives after a lengthy period of conflict. To facilitate this, the Ugandan government and donors have promoted investment in pigs as an important strategy for generating income quickly and ensuring livelihood security. In this context, animal health issues are an acknowledged challenge, creating uncertainty for animal owners who risk losing both their animals and income. This paper draws on policy documents guiding the veterinary sector, interviews with faculty staff at Makerere University and with veterinarians and paraprofessionals in northern Uganda, and ethnographic fieldwork in smallholder communities. The aims of this study were to contribute to an understanding of the structure of veterinary support and its dominant development narratives in policy and veterinary education and of the way in which dominant discourses and practices affect smallholders’ ability to treat sick animals. Particular attention was paid to the role of paraprofessionals, here referring to actors with varied levels of training who provide animal health services mainly in rural areas. The results suggest that veterinary researchers, field veterinarians and government officials in agricultural policy share a common discourse in which making smallholders more ‘business-minded’ and commercialising smallholder production are important elements in reducing rural poverty in Uganda. This way of framing smallholder livestock production overlooks other important challenges faced by smallholders in their livestock production, as well as alternative views of agricultural development. The public veterinary sector is massively under-resourced; thus while inadequately trained paraprofessionals and insufficient veterinary support currently present a risks to animal health, paraprofessionals fulfil an important role for smallholders unable to access the public veterinary sector. The dominant discourse framing paraprofessionals as ‘quacks’ tends to downplay how important they are to smallholders by mainly highlighting the negative outcomes for animal healthcare resulting from their lack of formalised training. The conclusions of this study are that both animal health and smallholders’ livelihoods would benefit from closer collaboration between veterinarians and paraprofessionals and from a better understanding of smallholders’ needs.